"Como faço se depois fico sem dupla?": afetividade e cognição de idosos com depressão em um jogo de tabuleiro moderno. - Barbosa, Anna Paula Sampaio (2019)
The psychological aspects related to aging and depression need to be further investigated due to the need of creating strategies of intervention in the context of the phenomenon of depression in elderly. This research aimed to investigate the elderly behavior with symptoms of depression in a set of rules (games). Participated of the workshops fourteen elderlies with an average age of 70 years old, where twelve were women and two were men. The participants were classified into two groups: G1, constituted by elderlies with depression symptoms and G2, the group of comparison, constituted by elderlies without depression symptoms. Symptoms of depression were measured using the Beck-II Depression Inventory. Posteriorly, pairs were formed with an individual from group G1 and another individual from group G2. Based on the Piagetian theory, we organized levels of heuristic analysis, ranging from level I, more rudimentar in terms of understanding, going through level IIA and IIB until level III, the most sophisticated. Besides, during the workshops, it was generated a protocol of evaluation of affective-emotional factors in which it was categorized behaviors facilitating and non-facilitating of (the individuals) performance. The instrument used was the game Gardens, created by the psychologist Perepau LListosella, which is a modern board game that mixes the mechanics of placing the pieces and construction from the model. Players work together building the board and need to exercise, among other things, spatial reasoning and memory. Throughout the workshops, participants played three game matches and were individually interviewed about their experiences during the project. The data show that G1 elderlies suggested had experienced more positive emotions during workshops compared to the results indicated by G2 elderlies, in addition the ones with symptoms of depression achieved better levels of performance in the game. Data also point to the need for spaces of support and social exchanges, such as a possibility of new cognitive constructions and affective development, especially for an elderly with depression. These spaces should favor dynamic and reciprocal interactions, through which protection processes can be produced even in the face of depression risk factors such as the social isolation. In this context, the peculiarities of modern board games, such as the need for players to keep alert, even when the partner is playing in order to rethink and organize its own strategie from the opponent's action. It seems to be crucial for the success of the intervention strategy as it helped players to stay focused on the activity and promoted a more immersive experience. We conclude that the use of the modern board game Gardens is fertile for programs of psychological management of the symptoms of depression in olde age, favoring the construction of protective factors, from the point of view of cognition and most especially from the affectivity